KWh Meter Monitoring System for Boarding House Payments using The BLYNK and ESP32 Applications - Ryan Hidayat; Rusmin Saragih; Husnul Khair (International Journal of Health Engineering and Technology, 2022)
The growth of electrical energy continues to increase from time to time in line with increasing economic activities and community welfare. The increasing growth of electrical energy will deplete existing non-renewable energy sources if their utilization is not effective and efficient. In the utilization of electrical energy it is not known how much energy has been used so that it tends to waste electrical energy. It is necessary to measure the use of electrical energy which aims to manage electrical energy which is very important so that the process of saving and efficiency can be obtained easily. This device is designed to replace the manual electrical energy measurement system because the data obtained cannot be done all the time and the results take too long to come out. This device consists of 4 (four) parts, namely sensors, microcontroller, display and network. The sensor used is the PZEM-004T sensor which is used to measure AC voltage and current, the microcontroller is used NodeMCU which will process the sensor results, the display uses a Liquid Crystal Display (LCD). ) type to display real time output data. The last part is the network as a place for permanent storage and further data processing.